Masonry failure analysis using a composite interface model - Kumar, Nitin; Rajagopal, A. (Journal of Structural Engineering, 2024)
In present paper a plasticity based composite interface model is propose for failure analysis of the masonry. The composite interface model consist of single surface yield criterion which is extension of Mohr-Coulomb criteria with cut in tension region and a cap in compression region. The inelastic behaviour include the softening of the tensile strength, cohesion, frictional angle and dilation angle, whereas for compression hardeningis considered. The model is the developed by using implicit backward-Euler integration strategy which is combined with a local/global. Newton solver based on a consistent tangent operator compatible with an adaptive sub stepping strategy.The interface model is implemented in standard finite element software (ABAQUS) by using user defined subroutine andfinally, constitutive verification examples are presented.